Analisis Penerapan Pasal 81 Undang-Undang Transfer Dana pada Putusan Nomor 78/Pid.Sus/2022/PN YYK Berdasarkan Asas Lex Specialis Sistematis - Qanita Fakhira; Valencia Lie; Shofie Nailasachi Puspadristia; Nurhidayah Muhcti; Nazila Rizka Hidaya; Addrey Ben Vitahula (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Electronic Fund Transfer is a fund transfer method that is often used because it saves time and costs. However, along with the development of Information and Communication Technology, this method is becoming increasingly vulnerable to cybercrime due to its implementation using electronic systems. In 2021, Oleksandr Chuiko, Maryna Kahalnytska, and Andrei Turskiy stole electronic information from Bank BRI ATM cards and transferred the data to World Elite ATM cards. This action violated Article 81 of the Transfer of Funds Act and Article 35 of the Electronic Information and Transactions Act. The main charge in this case, Article 81 of the Transfer of Funds Act, has sparked debate due to the defendants use of computer technology regulated by the Electronic Information and Transactions Law.